Adsorption of heavy metal ions on surface of functionalized oil palm empty fruit bunch fibers: single and binary systems - Mohd Shaiful Sajab; Chin, Hua Chia; Sarani Zakaria; Sillanpää, Mika (Penerbit Universiti Kebangsaan Malaysia, 2017)
The functionalization of surface charges on oil palm empty fruit bunch (EFB) fibers was modified by grafted carboxylic acid and polymer amine groups. Single and binary adsorption of Cu(II), Ni(II), Mo(VI) and As(V) were investigated by competitiveness in the adsorbents. The mechanism of each metal ion was deliberately studied on kinetics-diffusion (intraparticle diffusion) and isotherm adsorption models (Langmuir and Freundlich). Competitiveness of metal ions was found in the selectivity of Cu(II) > Ni(II) and Mo(VI) > As(V) in the binary solution. The regeneration of adsorbents was performed up to five cycles of an adsorption/desorption process and the reduction of adsorption performance was less than 14.5%. Therefore, this promises low-cost adsorbents for metal ion uptake, showing potential for removal and recovery in industrial wastewater treatment.